The outcome and complications of total parenteral nutrition in pediatric hematopoietic stem cell transplantation. (23rd November 2021) - Alsalamah, Shoug; Alramyan, Rana; Alakel, Raghad; Altheyeb, Fatema; Alrashed, Riyouf; Masuadi, Emad; Alyousif, Ghadah; Bin Sunaid, Faisal F.; Alsultan, Abdulrahman; Essa, Mohammed F.
Abstract: Background: Nutritional support posthematopoietic stem cell transplantation (HSCT) with total parenteral nutrition (TPN) or nasogastric tube feeding (NGT) in pediatric patients is associated with benefits and risks. Methods: We retrospectively reviewed the indication of TPN use in our pediatric HSCT patients and its impact on survival and possible related complications. Results: A total of 228 HSCTs were performed during the study period. TPN was used in 144 patients (63.2%) for a median of 14 days, while 8.8% had NGT feeding and 28% were able to tolerate oral feeding. Severe mucositis was seen in 104 TPN patients (72.2%) in comparison with 22 patients (26.2%) who were on Enteral Nutrition (EN) ( p = <.001). Sinusoidal obstruction syndrome (SOS) was seen in 19 (13.2%) patients who had TPN compared to none in the patients who received EN ( p = .001). The majority of patients who had SOS received myeloablative conditioning (MAC) therapy for hemoglobinopathy. Acute graft‐versus‐host disease (aGVHD) was seen in 24.8% of TPN patients and 9.1% of non‐TPN patients ( p = .01). However, there were no statistically significant differences in chronic GVHD, bacteremia, and patients' survival between both groups. Conclusions: TPN is commonly used after pediatric HSCT in cases of severe mucositis. NGT feeding was found to be the least used nutritional support method. SOS and aGVHD were associated more frequently in TPN patients compared to EN patients. This suggests the possible disadvantages of TPN and importance of SOS preventative measures in high‐risk patients.